“It’s Not All About Money”: Toward a More Comprehensive Understanding of Financial Abuse in the Context of VAW - Eriksson, Marie (Journal of interpersonal violence, 2021)
Men’s violence against women (VAW) is multifaceted and complex. Besides physical, psychological, and sexual violence, women subjected to VAW often suffer from economic hardship and financial abuse. Financial abuse involves different tactics used to exercise power and gain control over partners. Experiences of financial abuse make it difficult for women to leave an abusive partner and become self-sufficient. From an intersectional perspective, applying the concept of the continuum of violence, the aim of this article is to develop a more comprehensive understanding of how women subjected to men’s violence in intimate relationships experience the complexity of financial abuse in their lives, in the context of VAW. Based on 19 in-depth interviews with women surviving domestic violence, the study describes how intertwined women’s experiences of financial abuse are with other forms of abuse, influencing each other, simultaneously experienced as a distinct form of abuse with severe and longstanding consequences. Women in the study describe how men’s abuse affects them financially, causing poverty and affecting their ability to have a reasonable economic standard. Financial abuse also causes women ill health, and damages their self-esteem and ability to work, associate, and engage in social life. The interviewed women describe how experiences of financial abuse continue across time, from their past into their present situation and molding beliefs about the future. According to the interviews, financial abuse in private life sometimes continues into the public sphere, reproduced by social workers mimicking patterns of ex-partners’ abuse. Bringing out a more comprehensive understanding of the dynamic continuum of financial abuse, our results deepen knowledge about the complexity of VAW in women’s lives, and thereby are important in processes of making victims of violence survivors of violence.